How elementary school teachers assess students’ psychomotor during distance learning? - Dewi Ambarwati; Herwin Herwin; Shakila Che Dahalan (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2022)
Assessment of student learning is still carried out even at distance learning. This study aims to describe how elementary school teachers assess students' psychomotor during distance learning. This research is a qualitative research with the type of phenomenology. The subjects of this study were elementary school teachers, principals, parents, and students. The research data were collected using interview techniques and document studies. The data analysis technique used is interactive analysis through data collection, data condensation, data verification and drawing conclusions. The teacher begins the skills assessment by planning in advance. Planning begins with determining the competencies to be addressed, but the condition of the student's situation while at home is also a consideration for teachers in designing skills assessments. The implementation of the skills assessment is carried out through various platforms such as WhatsApp, Zoom, and Google Classroom. Teachers assess students' skills through photos and videos that students send on online platforms.